Prevalence, Mortality, and Indicators of Health Care Supply—Association Analysis of Cardiovascular Diseases in Germany - Dornquast, Christina; Willich, Stefan N.; Reinhold, Thomas (Frontiers in Cardiovascular Medicine, 2018)
Introduction: There are regional differences in the morbidity of major cardiovascular disease between the 16 federal states of Germany. An association between the morbidity and the health care supply has been described in international studies. The aim of the present analysis was to examine the relationship between the prevalence or mortality of major cardiovascular disease and several key indicators of health care supply in Germany. Methods: Life expectancy and the proportion of over 65-year old persons were included as characteristics to depict the general health. Indicators of health care supply were the number of general practitioners, internists, and cardiologists, number of internal medicine and cardiology beds, chest pain units, cardiac catheterization laboratories and stroke units. We compared the cardiovascular disease prevalence and mortality with these indicators and performed a weighted linear regression. Results: Regional variations between the federal states were found in general health and health care supply. The regression analysis yielded significant associations of the prevalence of major cardiovascular disease with the number of internal medicine hospital beds (p=0.045), cardiologists (p=0.031), and the number of residents per chest pain unit (p=0.036). Additionally, the relationship between cardiovascular mortality and also the number of residents per chest pain unit appeared to be significant (p=0.002). For all other indicators, no significant association was observed. Conclusions: We detected regional differences in the general health and health care supply between the 16 German federal states as well as several significant associations between cardiovascular morbidity and health care supply indicators. These results may aid in future development of health care systems.